Sources, seasonal cycling, and fate of plutonium in a seasonally stratified and radiologically contaminated pond - Naomi L. Wasserman; Nancy Merino; Fanny Coutelot; Daniel I. Kaplan; Brian A. Powell; Annie B. Kersting; Mavrik Zavarin (Scientific Reports, 2023)
Abstract Unlike short-term laboratory experiments, studies at sites historically contaminated with radionuclides can provide insight into contaminant migration behavior at environmentally-relevant decadal timescales. One such site is Pond B, a seasonally stratified reservoir within Savannah River Site (SC, USA) has low levels (μBq L−1) of plutonium in the water column. Here, we evaluate the origin of plutonium using high-precision isotope measurements, investigate the impact of water column geochemistry on plutonium cycling during different stratification periods, and re-evaluate long-term mass balance of plutonium in the pond. New isotopic data confirm that reactor-derived plutonium overwhelms input from Northern Hemisphere fallout at this site. Two suggested mechanisms for observed plutonium cycling in the water column include: (1) reductive dissolution of sediment-derived Fe(III)-(oxyhydr)oxides during seasonal stratification and (2) plutonium stabilization complexed strongly to Fe(III)-particulate organic matter (POM) complexes. While plutonium may be mobilized to a limited extent by stratification and reductive dissolution, peak plutonium concentrations are in shallow waters and associated with Fe(III)-POM at the inception of stratification. This suggests that plutonium release from sediments during stratification is not the dominant mechanism driving plutonium cycling in the pond. Importantly, our analysis suggests that the majority is retained in shallow sediments and may become increasingly recalcitrant.